Cardiovascular and Cerebral Responses During a Vasovagal Reaction Without Syncope - Aebi, Mathias R.; Bourdillon, Nicolas; Meziane, Hadj B.; Nicol, Edward; Barral, Jérôme; Millet, Grégoire P.; Bron, Denis (Frontiers in Neuroscience, 2019)
This clinical case report presents synchronous physiological data from an individual in whom a spontaneous vasovagal reaction occurred without syncope. The physiological data are presented for three main phases: Baseline (0-200 s), vasovagal reaction (200-600 s), and recovery period (600-1200 s). The first physiological changes occurred at around 200 s, with a decrease in blood pressure, peak in heart rate and vastus lateralis tissue oxygenation, and a drop in alpha power. The vasovagal reaction was associated with a progressive decrease in blood pressure, heart rate and cerebral oxygenation, whilst the mean middle cerebral artery blood flow velocity and blood oxygen saturation remained unchanged. Heart rate variability parameters indicated significant parasympathetic activation with a decrease in sympathetic tone and increased baroreflex sensitivity. The total blood volume and tissue oxygenation index dropped in the brain but slightly increased in the vastus lateralis, suggesting cerebral hypoperfusion with blood volume pooling in the lower body part. Cerebral hypoperfusion during the vasovagal reaction was associated with electroencephalography (EEG) flattening (i.e. decreased power in beta and theta activity) followed by an EEG high-amplitude “slow” phase (i.e. increased power in theta activity). The subject developed signs and symptoms of pre-syncope with EEG flattening and slowing during prolonged periods of symptomatic hypotension, but did not lose consciousness.